The Effect of Using the Ebumil Android Application on Knowledge and Independence of Pregnant Women about Pregnancy Care - Kartini, Kartini; Farming, Farming; Fitriati Sabur (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: This study aimed to analyze the effect of using the Ebumil Android application on the Independence and knowledge of pregnant women regarding pregnancy care. METHODOLOGY: This study employed a quasi-experimental design to investigate pregnant women at four Community Health Centres in Kendari City, spanning from April to October 2024. The study involved 120 pregnant women divided into two groups: those who were given an online application and those who received leaflets, using a simple random sampling technique. The study used the Friedman statistical test. RESULTS: The study found that the Intervention led to a significant increase in knowledge among the respondents compared to the control group. The intervention group showed a slight increase in knowledge at the second post, whereas the control group showed no growth. The p-value was < 0.05. The study found that online applications significantly increased knowledge about pregnancy care, with a faster increase in Independence compared to leaflets and a significant effect on the intervention and control groups (p = 0.000 for both knowledge and Level of Independence). CONCLUSION: Ebumil application can improve knowledge and level of Independence better than conventional leaflets.